Livestock-associated methicillin-resistant Staphylococcus aureus in Czech retailed ready-to-eat meat products - Gelbíčová, Tereza; Brodíková, Kristýna; Karpíšková, Renáta (International journal of food microbiology, 2022)
This study was aimed on the detection of methicillin resistant Staphylococcus aureus (MRSA) in different categories of retailed ready-to-eat (RTE) meat products from the Czech producers and determination of their genetic properties, antimicrobial resistance and virulence. In RTE meat products, 2% (4/181) of examined samples were MRSA positive. MRSA strains were detected only in durable fermented meat products made exclusively from pork meat. Detection of livestock-associated MRSA (LA-MRSA) clonal lineages (ST398 and ST4999), SCCmec cassette type V and tetracycline resistance indicate a source of contamination from raw pork. The study confirms the ability of these strains to survive the technological process rather than contamination of meat products from the food processing environment. MRSA strains did not carry any of the tested genes encoding staphylococcal enterotoxins or virulence genes (for Panton-Valentine leukocidin, exfoliative toxins A, B and toxic shock syndrome). Our results point out the spread of LA-MRSA through the meat processing chain.
Keywords: Animals; Česká republika; Livestock; Staphylococcal Infections; Microbial Sensitivity Tests; maso; zvířata; stafylokokové infekce; mikrobiální testy citlivosti; antibakteriální látky; methicilin rezistentní Staphylococcus aureus; Anti-Bacterial Agents; Czech Republic; Meat; Meat Products; dobytek; Methicillin-Resistant Staphylococcus aureus; masné výrobky